Hyperkalemic Recurrent Bilateral Lower Extremity Weakness in a Patient on Hemodialysis. (13th May 2012) - Hassen, Getaw Worku; Newstead, Suzanne; Giordano, Lorraine Maria
Abstract : Hyperkalemia is a severe life-threatening electrolyte disorder that commonly affects the cardiac conductivity and contractility. Ascending paralysis affecting the extremities with focal neurological deficit as well as quadriparesis and a seizure associated with hyperkalemia has been reported in the literature. Here, we describe a case of isolated recurrent lower extremity paralysis and an episode of seizure in an 83-year-old patient with end-stage renal disease on hemodialysis.